2020
DOI: 10.1101/gad.333997.119
|View full text |Cite
|
Sign up to set email alerts
|

Aurora B-dependent Ndc80 degradation regulates kinetochore composition in meiosis

Abstract: The kinetochore complex is a conserved machinery that connects chromosomes to spindle microtubules. During meiosis, the kinetochore is restructured to accommodate a specialized chromosome segregation pattern. In budding yeast, meiotic kinetochore remodeling is mediated by the temporal changes in the abundance of a single subunit called Ndc80. We previously described the regulatory events that control the timely synthesis of Ndc80. Here, we report that Ndc80 turnover is also tightly regulated in meiosis: Ndc80 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 81 publications
(134 reference statements)
3
24
0
Order By: Relevance
“… 37 CEN cluster 3 proteins associate with centromeres of cycling and meiotic metaphase I cells, but are depleted at prophase I. Consistently, this cluster included outer kinetochore complexes Ndc80c NDC80c and Dam1c, which are shed at prophase I due to specific degradation of Ndc80 NDC80 protein 25 , 38 , 39 ( Table S3 ). Direct comparison of the prophase I and metaphase I datasets revealed extensive changes in the composition of kinetochores upon prophase exit ( Figures 2B and 2C ).…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“… 37 CEN cluster 3 proteins associate with centromeres of cycling and meiotic metaphase I cells, but are depleted at prophase I. Consistently, this cluster included outer kinetochore complexes Ndc80c NDC80c and Dam1c, which are shed at prophase I due to specific degradation of Ndc80 NDC80 protein 25 , 38 , 39 ( Table S3 ). Direct comparison of the prophase I and metaphase I datasets revealed extensive changes in the composition of kinetochores upon prophase exit ( Figures 2B and 2C ).…”
Section: Resultsmentioning
confidence: 63%
“…At prophase I exit in wild-type cells, Ndc80 NDC80 is re-synthesized leading to outer kinetochore re-assembly and re-attachment to microtubules. 25 , 38 , 43 In mcm21Δ cells, however, Ndc80-GFP re-accumulation at kinetochores was delayed, and foci were fainter ( Figure 5A ). Where detected in mcm21Δ cells, individual Mtw1-tdTomato kinetochore foci tended to “spread,” rather than form bilobed clusters typical of metaphase I ( Figure 5B ), suggesting that residual outer kinetochore re-assembly is insufficient to support microtubule attachment.…”
Section: Resultsmentioning
confidence: 99%
“…3 D). The beginning of clustering, about thirty minutes before spindle assembly may correspond to the time at which new Ndc80 complexes, capable of interacting with microtubules, are added to the meiotic kinetochore (Meyer et al, 2015; Miller et al, 2012; Chen et al, 2020). This clustering does not occur in ndc80-md mutants that cannot produce new outer kinetochores after exiting prophase (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ectopic expression of Ndc80 in meiotic prophase causes chromosome missegregation (Miller et al 2012;Chen et al 2017), so this removal of Ndc80 is critical. The new work by Chen et al (2020) reveals how the cell protects itself from missegregation by removing Ndc80 from kinetochores. First, they found that when cells enter meiotic prophase, the Ndc80 subunit is phosphorylated along its N terminus by Ipl1 (Fig.…”
mentioning
confidence: 99%
“…Second, they found that phosphorylation of the Ndc80 N-terminal tail promotes the release of the kinetochores from microtubules as cells enter meiosis and the chromosomes begin identifying their homologous partners. Remarkably, as an added level of protection, Chen et al (2020) discovered that, in meiosis, the phosphorylation of Ndc80 results in targeted degradation of Ndc80. This degradation is specific to meiotic prophase; when expressed in metaphase I, the Ndc80 protein is stable.…”
mentioning
confidence: 99%